PENGARUH TARIF PAJAK, TUNNELING INCENTIVE, DAN INTANGIBLE ASSET TERHADAP KEPUTUSAN TRANSFER PRICING - Sherly Nur Haliyah, (2021)
This research is quantitive study that aims to determine the effect of tax rate, tunneling incentive and intangible asset on transfer pricing decision. In this reserach, the population is the company which listed at five sectors (basic material, consumer cyclicals, consumer non-cyclicals, healthcare and insdustrial) on IDX duing the period 2015 to 2019. The sample selection method used is purposive sampling and collected a sample of 110 research data. The hypothesis in this research was tested by Multiple Linear Regressian Analysis techniques with a significant level of 5%. The results showed that tax rate had no significant effect, tunneling incentive had a significant positive effect and intangible asset had no significant effect on the transfer pricing decision variable.